Endless: A Purine‐Binding RNA Motif that Can Be Expressed in Cells1. (9th July 2014) - Kröner, Christoph; Thunemann, Martin; Vollmer, Sven; Kinzer, Manuela; Feil, Robert; Richert, Clemens
Abstract It is becoming increasingly clear that nature uses RNAs extensively for regulating vital functions of the cell, and short sequences are frequently used to suppress gene expression. However, controlling the concentration of small molecules intracellularly through designed RNA sequences that fold into ligand‐binding structures is difficult. The development of "endless", a triplex‐based folding motif that can be expressed in mammalian cells and binds the second messenger 3′, 5′‐cyclic guanosine monophosphate (cGMP), is described. In vitro, DNA or RNA versions of endless show low micromolar to nanomolar dissociation constants for cGMP. To test its functionality in vivo, four endless RNA motifs arranged in tandem were co‐expressed with a fluorescent cGMP sensor protein in murine vascular smooth muscle cells. Nitric oxide induced endogenous cGMP signals were suppressed in endless‐expressing cells compared to cells expressing a control motif, which suggests that endless can act as a genetically encoded cGMP sink to modulate signal transduction in cells.